2017
DOI: 10.1093/cercor/bhw419
|View full text |Cite
|
Sign up to set email alerts
|

Task Context Overrules Object- and Category-Related Representational Content in the Human Parietal Cortex

Abstract: The dorsal, parietal visual stream is activated when seeing objects, but the exact nature of parietal object representations is still under discussion. Here we test 2 specific hypotheses. First, parietal cortex is biased to host some representations more than others, with a different bias compared with ventral areas. A prime example would be object action representations. Second, parietal cortex forms a general multiple-demand network with frontal areas, showing similar task effects and representational conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
120
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(157 citation statements)
references
References 54 publications
22
120
5
Order By: Relevance
“…By examining responses in an action and an object category task, using fMRI MVPA, Bracci et al (2017) reported greater task modulation of visual representation in parietal than in occipitotemporal region, with no representation found in parietal region for the task-irrelevant information. Although their overall conclusion is consistent with ours, the use of an event-related design likely weakened the effect and prevented them from observing the representation of the task-irrelevant information in the dorsal region.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…By examining responses in an action and an object category task, using fMRI MVPA, Bracci et al (2017) reported greater task modulation of visual representation in parietal than in occipitotemporal region, with no representation found in parietal region for the task-irrelevant information. Although their overall conclusion is consistent with ours, the use of an event-related design likely weakened the effect and prevented them from observing the representation of the task-irrelevant information in the dorsal region.…”
Section: Discussionmentioning
confidence: 99%
“…However, both monkey and human studies over the last two decades have reported robust representations of a variety of "what" information in the dorsal pathway (Sereno and Maunsell, 1998;Sawamura et al, 2005;Janssen et al, 2008;Konen and Kastner, 2008;Liu et al, 2011;Christophel et al, 2012;Hou and Liu, 2012;Ester et al, 2015;Xu and Jeong, 2015;Bettencourt and Xu, 2016;Bracci et al, 2016;Freud et al, 2016;Jeong and Xu, 2016). These findings challenge the two-pathway view and argue for a convergence between the two pathways.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations